Action Plan : Westhaven Neighborhood Committee - Westhaven Neighborhood Committee (2017)

Supporting English-speaking Children and Families in the Gaspé and Magdalen Islands 2017-2020 - Community Health and Social Services Network (CHSSN); Council for Anglophone Magdalen Islanders (CAMI); Vision Gaspé-Percé Now; Committee for Anglophone Social Action (CASA) (2017)
The official language minority community of this region has the poorest socioeconomic status in Canada when aspects such as low education levels, unemployment and low income tendencies are analyzed. Children are particularly affected by this status. Children ages 0 to 5 make up 6.6% of the total English-speaking population.
Keywords: Official Language Minority Community (OLMC)